Peran Digital Humanities dalam Upaya Regenerasi Sumber Daya Manusia untuk Mewujudkan Pembangunan Pertanian Berkelanjutan - Sunarru Samsi Hariadi; Ari Widya Handayani; Puri Eka Dewi Fortuna (Jurnal Kawistara, 2022)
Digital humanities is a meeting point between the humanities and the technological sciences with the aim of studying the use of digital tools in aspects of the humanities and how the humanities affect technology. Regarding the development of digital humanities and sustainable agricultural problems, this research is focused on looking at the interest of young people working in agriculture.  The purpose of this study is to find out: how the role of digital media (digital humanities) affects the interest of youth working in agriculture so that it can be realized the regeneration of agricultural human resources, what factors affect the interest of youth to work in agriculture, predicting the younger generation who will work in agriculture as an effort to regenerate in agriculture. The study was conducted in Klaten and Temanggung districts with 106 small samples of youth taken at random. To predict the younger generation who will work in agriculture using qualitative and quantitative statistical path analysis. The results stated that youth's interest in working in agriculture is influenced by youth attitudes towards the agricultural sector, social media utilization, self-efficacy, and the role of parents. The use of social media affects the attitude of youth in agriculture and youth self-efficacy. Efforts that can be made to increase the interest of youth working in agriculture include strengthening self-efficacy and attitudes in agriculture by optimizing the role of parents and the use of social media to get information in agriculture.